The World Bank as an International Financial Institution - Rasul Shams (Hamburg Institute of International Economics (HWWA), 2004)
The World Bank is a prestigious and large international financial institution. Since its foundation it has widened the scope and the size of its activities. One interpretation of what the World Bank is doing is the provision of public goods. If we take this interpretation seriously the comprehensiveness of the Bank's activity suggests that the Bank is assuming more and more the functions of a world government in the making. An alternative interpretation would look at the World Bank as a huge bureaucratic organization, acting on its own behalf. This interpretation can not be endorsed fully by the available information, but only in the sense of bureau-shaping. The Bank itself is proud of being a knowledge bank. But its actual activity is the popularization of ideas on development and not the application of research outcomes in its day-to-day operations. The most appropriate interpretation of the activity of the World Bank is that its changing scope and size is shaped heavily by pressure from different interest groups.
Keywords: O1; G21; F34; F33; 330; international lending; economic development; public goods; interest groups; Entwicklungsbank; Internationale Wirtschaftsorganisation; Internationale Kreditvergabe; Entwicklungshilfe; Öffentliches Gut; Interessenpolitik; Welt; International Bank for Reconstruction and Development